Study on the usefulness of the present health information system for management of family planning at peripheral level. - Perera, H.S.R (My University, 1998)
This study was undertaken to identify the strengths and weaknesses in the present HIS for family planning (FP) with a view to studying the use of infromation as a management tool in the FP program,at the divisional and sub divisional levels.Five (5) different interventions were identified based the findings of the first part of the study.The interventions were:training program for all health workers in all five areas(A-E) ; introduction of evaluation formats to be used at monthly conferences(area B) ; introduction of a self assessment checklist to PHMs (area C); all these three components (area D) and introduction of a modified field record(area E).Introduction of the evaluation foramat along with the educational program was the most effective intervention, which enhanced the use and improved the knowledge for use of information at the peripheral level. The modified field record improved the quality of record keeping.These findings highlight the need for educational programs to be linked with activities in which the knowledge could be applied.Most of the interventions studied did not need additional resources,hence the need to consider the feasibility of introducing similar programs and follow up for a longer period than was done during this study,to assess the sustainability.